CAROTID INTIMA MEDIA THICKNESS— A VALUABLE TOOL IN ASSESSING SUBCLINICAL ATHEROSCLEROSIS PROGRESSION IN OBESE CHILDREN - Mihuta, Monica Simina; Paul, Corina; Borlea, Andreea; Cepeha, Cristina Mihaela; Stoian, Dana (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVE After the COVID-19 pandemic, the prevalence of obesity among children is higher than ever. The carotid intima- media thickness (CIMT), a predictor of atherosclerotic prog- ression, correlates with most of the clinical and paraclinical parameters used for the assessment of obese patients. Our objective is to show that CIMT can be used in the assessment of subclinical atherosclerosis in obese children. METHODOLOGY We analyzed 85 patients aged 6–18 years old by measuring their CIMT using the Aixplorer MACH 30 echography machine - automatic measurement software. Three study groups were defined: obese, overweight and normal weight. The analysis focused on correlations between correlates and BMI, waist circumference, Tanner puberty stages and blood pressure as clinical tools, and to the usual blood parameters: lipid panel, triglycerides and fasting glucose. RESULTS Obesity and abdominal adiposity in children is linked to increased CIMT. Waist circumference and TG/HDL-C ratio are significant predictors of CIMT. Higher values for CIMT were detected in children with Tanner 4 and 5 development stages (p<0.041). Children with blood pressure values over the 95th percentile presented higher values for CIMT, regardless of their BMI. HDL-C, LDL-C, total cholesterol and triglycerides were correlated with CIMT; fasting glucose was not. CONCLUSION Expected values of the CIMT are influenced by the severity of the obesity. Abdominal adiposity of obese children is reliably correlated with CIMT values. High blood pressure is correlated to higher CIMT values, regardless of the patients’ BMI. All evaluated blood parameters, except for fasting glucose, showed correlations with CIMT.